Clinical evaluation of acute necrotizing encephalopathy in children - Fan, Xiaowei; Huang, Li; Li, Suyun; Yang, Sida; Song, Yongling; Chen, Qinglian; Xiong, Yumei; Peng, Qiuyan; Ma, Wencheng; Hu, Dandan; Li, Peiqing (Frontiers in Pediatrics, 2022)
Objective: Acute necrotizing encephalopathy (ANE) is a rare but severe encephalopathy and is associated with a high morbidity and mortality. We aimed to analyze and compare the clinical features and predictive indicators of pediatric ANE. Methods: This retrospective study included children with ANE diagnosed at Guangzhou Women and Children’s Medical Center between November 2018 and January 2020. Pediatric patients’ information, including clinical characteristics, laboratory tests, neuroelectrophysiology and brain magnetic resonance imaging (MRI) findings, MRI score, brainstem auditory evoked potential (BAEP) grades, ANE severity scores (ANE-SS), and modified Rankin scale (mRS), were collected. Results: Twelve ANE patients were included. Among them, one patient (8.3%) died from brainstem dysfunction, one (8.3%) recovered and ten (83.3%) experienced neurological sequelae. All patients had an initial viral infection and neurological symptoms such as acute disturbance of consciousness (ADOC) or seizure, and the interval from onset of the disease to neurological manifestations was 3 (1.25-3) days. MRI score-Ⅰ ranged from 1-3 (1.8±0.7), MRI score-Ⅱ ranged from 1-4 (2.5±1.1). ANE-SS varied from 1-6 (3.9 ± 1.3). The scores of mRS were from 0 to 6 (2.9 ± 1.7). Higher MRI score were associated with worse outcomes, while the BAEP grade and ANE-SS score were not significantly associated with mRS. Conclusion: ANE is a severe encephalopathy syndrome with rapid progression, resulting in serious neurological sequelae. Compared with BAEP grade and ANE-SS, brain MRI shows more comprehensive advantages in predicting the prognosis of ANE patients. More in-depth research and better indicators are still needed to support the evaluation and treatment of ANE.